A Feminist Stylistic Analysis in Taylor Swift’s Song “The Man” - Helena Gadis Deameysa; Dwi Leyla Sari; Dwi Leyli Ningsih; Indira Khofifah; Elviona (EDUPEDIA Publisher, 2023)
The Man” by Taylor Swift is a song about feminism and gender inequality which happened in Taylor swift’s life. This song was released on August 23th 2019. The research is qualitative descriptive research by collecting data with note taking technique through in-depth observation and analysis of the language used in the song lyrics. Taking into the social experiences of a woman to identify the feminist stylistics elements found in the song. There are several review theories that exist in the song lyrics. To convey the complexity of gender issues in a way how feminist stylistics works. The result is a woman is always demeaned and a man is always exalted in a community environment. Just because of the different perspectives of society that glorify men as more powerful and independent than women, women feel unfair because of gender inequality. This attracted the attention of Taylor Swift in bringing the song to the music media with her experiences in the entertainment world